METHODOLOGICAL FEATURES OF TEACHING PROGRAMMING LANGUAGES IN SECONDARY SCHOOL - Madyarova Г.А.; Eshenkozhayev1 Н.Ш. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
This article discusses the methodological features of teaching Python programming language in computer science in the 6th grade of secondary school. Based on the theoretical foundations of teaching in high school, a course on computer science in the programming language is developed. In the course of this research, an experiment was conducted at a secondary school in Almaty, and the training course was tested in practice. As a result of the research, a course on teaching the Python programming language will be developed on the Canvas LMS platform. The methodological and technical content of the course is disclosed. Pre-experimental and post-experimental learning indicators of students are shown. Students become more interested in programming and become accustomed to problem solving. This course can be used for synchronous and asynchronous learning during a pandemic. Research in this area is promising, as programming is one of the skills needed in the future.